Cationic polycarbonate-grafted superparamagnetic nanoparticles with synergistic dual-modality antimicrobial activity. (24th February 2016) - Pu, Lu; Xu, Jinbao; Sun, Yimin; Fang, Zheng; Chan-Park, Mary B.; Duan, Hongwei
Abstract : Grafting cationic polycarbonates on superparamagnetic nanoparticles leads to synergistic antimicrobial activities of cationic charge induced membrane disruption and magnetic heating. Abstract : We report a new class of antimicrobial nanomaterials with biodegradable cationic polycarbonates grafted on superparamagnetic nanoparticles. Our results have shown that end-functionalized cationic polycarbonates, synthesized by organocatalytic ring opening polymerization, can be grafted onto superparamagnetic MnFe2 O4 nanoparticles via ligand exchange. In comparison with the individual building blocks, the core–shell hybrid nanoparticles led to improved antimicrobial activities in two ways: first, the cationic polycarbonates in a brush form afforded a greater charge density than that of free polymer chains, resulting in stronger interactions with bacterial surfaces. Second, the structural integration of the "soft" polycarbonate shell and the "hard" superparamagnetic core in the hybrid nanoparticles brings about a synergistic action of membrane disruption by the cationic shell and magnetic hyperthermia by the nanoparticle core. The combination of two physical killing mechanisms holds great promise in fighting against a broad spectrum of bacterial pathogens.